Catheter-related venous thrombosis in NICU: A case-control retrospective study. Issue 1 (January 2022) - Chojnacka, Karolina; Krasiński, Zbigniew; Wróblewska-Seniuk, Katarzyna; Mazela, Jan
Introduction: Newborns treated in a neonatal intensive care unit (NICU) are susceptible to several complications one of them being vein thrombosis. Aim: The study aims to evaluate risk factors of catheter-related venous thrombosis, clinical manifestations, treatment, and the outcomes of thrombotic events (TE) during the neonatal period. Methods: This work is a case-control retrospective study performed on patients in the tertiary NICU between January 2013 and June 2016. The analysis includes data from infants with CVC diagnosed with thrombosis and infants with CVC, not being diagnosed with thrombosis (control group). Statistica 10 software was used for statistical analysis. Results: Vein thrombosis was diagnosed in 19 NICU infants including 16 cases of catheter-related vein thrombosis (84% of complicated cases). Other statistically significant risk factors were asphyxia, infection, and the duration of CVC use. The incidence of thrombosis in our population increased during the study which may result from a statistically significant increase in the number of inserted CVC (294 vs 435), and more frequent diagnosis of incidental thrombosis (1 vs 9). Conclusion: Vein catheterization, asphyxia, infection, and prolonged CVC use are critical risk factors for thrombosis in the neonatal period. Given the hereinbefore mentioned increased number of central line catheterizations in the NICU, it would be useful to conduct a prospective study with a scheduled routine ultrasound protocol applied not only as a tool to diagnose thrombosis but also to prevent it by determining a proper catheter for a particular vein.